2021
DOI: 10.1016/j.celrep.2020.108581
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Orthogonal Tiling from the Retina to the Visual Cortex

Abstract: Highlights d Orthogonal organization of visual tuning maps is observed in both V1 and the retina d Cortical tuning maps are correlated with the profile of ON-OFF feedforward projections d The profile of ON-OFF receptive fields varies periodically across the V1 and retina d Regularly structured retinal mosaics initiate the orthogonal tiling of the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…Notably, the current result also suggests a possible scenario through which to understand how viewpoint invariant selectivity can arise in infant animals. From the similarities between the CNN and the biological brain models, i.e., that the fundamentals of both CNNs and sensory cortices are based on the hierarchical feedforward structure and that the process of convolution via weight sharing in CNNs can be approximated by a biological model 73 76 of periodic functional maps with hypercolumns in the visual cortex, our result may inspire insight into how innate invariance can arise in infant animals.…”
Section: Resultsmentioning
confidence: 90%
“…Notably, the current result also suggests a possible scenario through which to understand how viewpoint invariant selectivity can arise in infant animals. From the similarities between the CNN and the biological brain models, i.e., that the fundamentals of both CNNs and sensory cortices are based on the hierarchical feedforward structure and that the process of convolution via weight sharing in CNNs can be approximated by a biological model 73 76 of periodic functional maps with hypercolumns in the visual cortex, our result may inspire insight into how innate invariance can arise in infant animals.…”
Section: Resultsmentioning
confidence: 90%
“…The theory predicts that the organization of a visual cortical map should be determined by the retinal position of ON and OFF ganglion cells sampling visual space with the two eyes, as proposed by previous retinal models 8,12,15,41,42 . However, unlike previous retinal models, the theory does not require (and does not rely on) a Moire interference of ON and OFF retinal arrays to generate orientation maps.…”
Section: Resultsmentioning
confidence: 92%
“…Surprisingly, although visual cortical maps are very diverse across species, the mapping of stimulus orientation can be strikingly similar in different mammalian orders such as primates, carnivores and scandentia 1,3,6 . This puzzling balance between map similarity and diversity has been the topic of intensive research over the past decades and inspired a large number of computational models [7][8][9][10][11][12][13][14][15][16] . However, while previous models were very successful at simulating general map patterns for some stimulus dimensions, they were challenged by the use of limited biological constraints and the complexity of simulating inter-related topographies for a large number of stimulus dimensions that include spatial position, eye dominance, light-dark polarity, orientation, spatial resolution, stimulus selectivity, and receptive field structure.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, deep neural network (DNN) models, which have a biologically inspired hierarchical structure, provide an effective approach for investigating functions in the brain (Paik and Ringach, 2011;DiCarlo et al, 2012;Yamins and DiCarlo, 2016;Sailamul et al, 2017;Baek et al, 2020Baek et al, , 2021Jang et al, 2020;Kim et al, 2020Kim et al, , 2021Park et al, 2021;Song et al, 2021). Several studies have reported that DNNs trained to natural images can predict the neural responses of the monkey inferior temporal cortex (IT) (Cadieu et al, 2014;Yamins et al, 2014), known as the area for object recognition.…”
Section: Untrained Alexnetmentioning
confidence: 99%
“…A model study using a biologically inspired deep neural network (DNN) (Krizhevsky et al, 2012; Simonyan and Zisserman, 2015) has been suggested as an effective approach to this problem (Paik and Ringach, 2011; DiCarlo et al, 2012; Yamins and DiCarlo, 2016; Sailamul et al, 2017; Baek et al, 2020, 2021; Jang et al, 2020; Kim et al, 2020, 2021; Park et al, 2021; Song et al, 2021). DNNs consist of a stack of feedforward projections inspired by the hierarchical structure of the visual pathway and can be used as simplified model to investigate various visual functions.…”
Section: Introductionmentioning
confidence: 99%